HUMAN RESOURCES EMPOWERMENT STRATEGY IN BUSINESS ACTIVITIES AND TOURISM DEVELOPMENT IN LAGUNA KAUR BEACH - Saputra, Julian; Darmawan, Dedy Darmawan; Islamiah, Farida (Universitas Ichsan Sidenreng Rappang, 2023)
Kaur Regency has a very good opportunity to boost regional competitiveness both at the regional and national levels, especially for a number of goods that have competitiveness in the tourism industry. The purpose of this research is to learn more about the training offered by the Office of Tourism and Creative Economy to tourism industry players in Laguna Beach. A descriptive approach is used in this qualitative research. Using observation, documentation, and interviews as data collection methods. To obtain sufficient data, information is collected from various sources. This information is then examined qualitatively and explained using words and phrases. The data analysis method used is data reduction, data visualization, and drawing conclusions. The findings of this study indicate that the training-based empowerment plan for Laguna Beach tourism business actors has been going quite well. This can be seen from the fact that business actors are given the necessary skills to manage beach tourism properly and effectively.